(untitled) (Anclajes, 2021)
The article deals with biographical mediation in Latin America. It examines the process of construction and deconstruction of the life of an emblematic 19th century Cuban poet: Julián del Casal. The poem “Oda a Julián del Casal” (1963) by José Lezama Lima, written for the centenary of Casal’s death, reflects on the possibility of building a vital poetic life as an alternative to the Cuban literary and cultural system. This question about the meaning of life, made by one poet to another, underlines the disruptive mode of creation that the Lezamian position enables, from “Julián del Casal” (1941) and “Oda a Julián del Casal” (1963), to the essays on Casal by Antonio José Ponte in El libro perdido de los origenistas (2004).